Variations of interfacial thermal conductance at melting and crystallization of an indium micro-particle in contact with a solid. (March 2021) - Minakov, A.; Morikawa, J.; Ryu, M.; Zhuravlev, E.; Schick, C.
Abstract: The heat transfer between a micrometer-sized particle, as used in laser-assisted additive manufacturing, and a substrate strongly depends on the variations in interfacial thermal conductance (ITC), among other thermophysical parameters of the sample and substrate. Variations of ITC were measured on a millisecond time scale during fast melting and crystallization of an indium micro-sized sample with a mass of about 1 ng. Fast scanning nanocalorimetry was simultaneously applied with high-speed infrared thermography. The ITC between the sample and the sensor membrane was obtained. Therefore, the evolution of the temperature difference at the sample/membrane interface during fast melting and crystallization of the micro-sized indium droplet was measured. An unusual effect of gradual variation of ITC in the melting experiment was found. The method can be applied for ITC measurements during fast processes with 0.26 ms resolution. The quantification of ITC allows, for example, the optimization of melting during additive manufacturing. Graphical abstract: Unlabelled Image Highlights: Interfacial thermal conductance for a micrometer-sized sample with a time resolution of 0.26 ms. Interfacial thermal conductance accessible before and during melting-solidification of 1 ng indium. Interfacial thermal conductance jumps and then gradually increases below the melting point.